ПЕРСПЕКТИВИ ПРАВОВОГО РЕГУЛЮВАННЯ ПОХІДНОГО ПОЗОВУ В УКРАЇНІ - Hudima, T.S.; Herasymenko, N.O. (Економіка та право, 2016)
The legal regulation of “the indirect claim” both in Ukraine, and at the international level is analysed in article. It is defined that the domestic legislation in this sphere is imperfect and nullifies the valid mission of this institute. Shortcomings of legal regulation of “the indirect claim” of Ukraine are revealed and ways to their elimination are offered. REFERENCES1. The Verkhovna Rada of Ukraine (2015), Pro vnesennya zmin do deyakykh zakonodavchykh aktiv Ukrayiny shchodo zakhystu prav investoriv: Zakon Ukrayiny [On amendments to some legislative acts of Ukraine on protection of investors’ rights: The Law of Ukraine], Vidomosti Verkhovnoi Rady Ukrainy, vol. 25, p. 1882. Kovalyshyn O.R. (2013), Sudovyy zakhyst korporatyvnykh prav [Judicial protection of corporate rights], abstract PhD. diss., commercial law, economic and procedural law, National Academy of Sciences of Ukraine, Research Institute of Private Law and Entrepreneurship, Kiev, Ukraine3. Ostrovs’ka L.A. (2008), Nepryami (pokhidni) pozovy: mizhnarodnyy dosvid ta zakonodavstvo Ukrayiny [Indirect (derivatives) claims: international experience and legislation Ukraine], abstract PhD. diss., civil law and civil procedure; family law; international private law, National Academy of Law of Odessa, Odessa, Ukraine4. Murashko N. (2016), Uprovadzhennya pokhidnoho pozovu: v chomu prorakhuvalysya deputaty [The introduction of the original claim: what miscalculated deputies], Forbs, available at: http://forbes.net.ua/ua/opinions/1413473-uprovadzhennya-pohidnogo-pozovu-v-chomu-prorahuvalisya-deputati (Accessed 7 October 2016)5. Pavlenko V. (2015), Shchyt chy mech dlya investora? [The shield or sword for investors?], Zakon i biznes, vol. № 27 (1221), available at: http://zib.com.ua/ru/print/117269-akcioneram_i_rukovoditelyam_predpriyatiy_sleduet_podgotovits.html (Accessed 7 October 2016)6. The Verkhovna Rada of Ukraine (2003), Tsyvil’nyy kodeks Ukrayiny [Civil Code of Ukraine], Ofitsiynyy visnyk Ukrayiny, vol. 11, p. 4617. The Verkhovna Rada of Ukraine (2003), Hospodars’kyy kodeks Ukrayiny [Economic Code of Ukraine], Ofitsiynyy visnyk Ukrayiny, vol. 11, p. 4628. The Verkhovna Rada of Ukraine (2012), Pro systemu harantuvannya vkladiv fizychnykh osib: Zakon Ukrayiny [About system guaranteeing deposits of individuals: The Law of Ukraine], Vidomosti Verkhovnoi Rady Ukrainy, vol. 50, p. 5649. Supreme Economic Court of Ukraine (2015), Postanova u spravi # 922/2029/15 [Resolution on the case number 922/2029/15], Yedynyy derzhavnyy reyestr sudovykh rishen’, available at: http://www.reyestr.court.gov.ua/Re view/53859310 (Accessed 7 October 2016)10. Supreme Economic Court of Ukraine (2015), Postanova u spravi # 910/16747/13 [Resolution on the case number 910/16747/13], Yedynyy derzhavnyy reyestr sudovykh rishen’, available at: http://www.reyestr.court.gov.ua/Review/46604521 (Accessed 7 October 2016)